Artificial Intelligence: An Essential Component for Libraries in the Digital Age (A Literature Review) - Wenda Ifani Hamidah; Rostika Yuliani; David Alusine Ceesay (Department Library of Governance Institut of Home Affairs, 2026)
Background/Problem Statement: Information technology induces profound transformations in individuals' approaches to information retrieval, enabling libraries to enhance their services through the integration of these technological advancements. The integration of technology-driven services, including Artificial Intelligence, presents a potential avenue for enhancing library offerings. Nonetheless, libraries are unable to adopt AI without adequate preparation.Purpose: to enhance exploration concerning the applications of AI services within the library context and the necessary preparations required. Method: This study utilized a literature review methodology, examining scholarly articles concerning Artificial Intelligence in library services published from 2020 to 2025. The chosen literature was sourced from esteemed academic databases and examined using thematic content analysis to uncover applications of AI and factors related to library readiness. Result: The findings of this research highlight various domains within AI that can be utilized in libraries, including natural language recognition, computer vision, speech recognition, and robotics. The establishment of the library for the implementation of AI involves the allocation of resources, consideration of user needs, attention to hardware and software elements, and support from a sufficient network infrastructure. Conclusion: The study arrives at the conclusion that AI has emerged as an essential component for libraries in the age of information technology. Nonetheless, effective execution hinges on the preparedness of the organization, encompassing fiscal backing, personnel resources, technological frameworks, and service planning centered around user needs.